Mothers, peers and gender-role identity - Claudia Olivetti; Eleonora Patacchini; Yves Zenou (Research Institute of Industrial Economics (IFN), 2019)
We study whether a woman's labor supply as a young adult is shaped by the work behavior of her adolescent peers' mothers. Using detailed information on a sample of U.S. teenagers who are followed over time, we find that labor force participation of high school peers' mothers affects adult women's labor force participation, above and beyond the effect of their own mothers. The analysis suggests that women who were exposed to a larger number of working mothers during adolescence are less likely to feel that work interferes with family responsibilities. This perception, in turn, is important for whether they work when they have children.
Keywords: J22; Z13; 330; Role models; Identity; Female labor supply; Peer effects; Work-family conflict